2022
DOI: 10.3389/fnut.2022.1041608
|View full text |Cite
|
Sign up to set email alerts
|

Microbial succession and its correlation with the dynamics of volatile compounds involved in fermented minced peppers

Abstract: Fermented minced peppers are a traditional fermented food that has a unique flavor due to various microbial communities involved in fermentation. Understanding the changes in microbial communities and volatile components of fermented minced peppers is particularly important to unveil the formation of unique flavor of fermented peppers. In this study, the microbial communities and volatile compounds in fermented minced pepper was analyzed by high-throughput sequencing and GC-MS, as well as their underlying corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Some studies have shown that Pichia can use glucose to produce a large number of volatile flavor substances, such as phenylethanol, 3-methylbutanoic acid, and ethyl linoleate, etc. [56]. Rhizopus promotes the production of amylase, which can break down starch into glucose and is metabolized to produce alcohols, acids, and other flavor substances [45].…”
Section: Correlation Analysis Of Microbial and Flavor Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that Pichia can use glucose to produce a large number of volatile flavor substances, such as phenylethanol, 3-methylbutanoic acid, and ethyl linoleate, etc. [56]. Rhizopus promotes the production of amylase, which can break down starch into glucose and is metabolized to produce alcohols, acids, and other flavor substances [45].…”
Section: Correlation Analysis Of Microbial and Flavor Compoundsmentioning
confidence: 99%
“…Foods 2024, 13, x FOR PEER REVIEW 14 of 18 methylbutanoic acid, and ethyl linoleate, etc. [56]. Rhizopus promotes the production of amylase, which can break down starch into glucose and is metabolized to produce alcohols, acids, and other flavor substances [45].…”
Section: Correlation Analysis Of Microbial and Flavor Compoundsmentioning
confidence: 99%